Knowledge and attitude of emergency physician about the emergency management of tooth avulsion - Laila A. Bahammam (BMC, 2018)
Abstract Background The aim of the study was to evaluate the knowledge of ER physicians with different specialties, experience and hospital sectors for the management of avulsed teeth in the emergency rooms of eight major hospitals in Jeddah, Saudi Arabia. It also covers their attitude towards receiving further education on tooth avulsion management. Methods A cross-sectional survey was conducted at the emergency rooms of eight hospitals in Jeddah from August to December 2015. A self-administered questionnaire consisting of 31 multiple choice questions assessing both knowledge and attitude was distributed to 150 physicians who were working in the ER departments. Results Response rate was 81.33%. Data revealed that 45.9% of the respondents did not have prior knowledge about avulsion. Physicians working in military hospitals had better knowledge about the ER management of avulsion cases than physicians of public hospitals. 80.3% of participants showed willingness to replant the tooth, however, 65.3% would not do it by themselves. 42.6% of the physicians did not know the importance of extra-oral time. Milk was selected as the best transport media for avulsed tooth by 31.1% of the participants. Regarding physicians' attitude, 95.1% showed interest in receiving information about the subject. Conclusion This study revealed that the majority of ER physicians lack the knowledge needed to manage avulsions cases. Hence, educational programs are necessary for ER physicians to provide proper management for those cases.